Impact of e-recruitment strategies in enterprises of the Republic of Kosovo - Dragusha, Blerim; Josimovski, Sasho; Jovevski, Dimitar (ILIRIA International Review, 2019)
In the modern world information technology especially internet is rapidly changing the way individuals interact in the real world in the labor force market. Social networks (SN) like Facebook, LinkedIn, Twitter; Instagram etc. has invaded our daily lives. Human resources management has also taken its share of these changes. Employers have begun using social networks for getting information about job candidates. Information provided by Social Network about personal and professional life of potential job candidates made Social Network as an important tool for recruiters. In the Republic of Kosovo even in some other countries social network is not an official part of the selection but their influence on the recruitment process is very evident. The essence of the research is the impact of social networks and traditional methods - interviews, C.V and recommendations in the recruitment process in the Republic of Kosovo. In foretold, the research thesis is explored with all the justifications and challenges that follow. Presentation of the research plan and procedures reflects in detail the real situation. The methodology I have used in this research has analytical character and practical verification of hypotheses. This first research is dealt with on this day and will be a major contributor to the human resources strategy devoted to the recruitment process. In the survey we made and the hypothesis that I have argued about the reality of the recruitment process in the Republic of Kosovo. And I conclude that: Social networks are effective and efficient in the recruitment process, it has the potential to find the best candidate for employment, has a competitive advantage. Link the social network with more reliable and professional social connections between social networks and traditional recruitment methods foresee them as a model of the future. But the replacement of traditional recruitment methods with social networks respondents now has rejected it as a possibility.
Keywords: Human Resource Management; Social Networks; Strategic Management; e Recruitment; Employment; e Business; Labour market